Limitations of Normal CSF Cell Counts in Excluding Bacterial Meningitis: A Multicentric Hospital Based Study in Kathmandu, Nepal - Sharma, Supriya; Acharya, Jyoti; Thapa, Jeewan; Khadka, Dhruba Kumar; Aryal, Shreedhar; Kayastha, Madhusudan; Sharma, Saroj; Sharma Chalise, Bimal; Bhandari, Parmananda; Karn, Ragesh; et al. (Journal of Institute of Science and Technology, 2024)
An increase in cerebrospinal fluid (CSF) cell count is an indicator of the diagnosis of bacterial meningitis. However, studies have reported that few bacterial meningitis cases showed no abnormalities in initial CSF analysis. Therefore, this study aimed to analyze the CSF cell count in culture positive bacterial meningitis cases. A cross-sectional hospital based prospective study was conducted from January 2017 to December 2018 among 387 CSF samples collected from clinically suspected meningitis cases attending different hospitals located in Kathmandu, Nepal. Each sample was processed for bacterial culture, total and differential leucocyte count, and protein and glucose concentration determination. Among the total CSF specimens (n=387), 32 (8.27%) were positive by culture for bacterial isolates. Bacteria were isolated from more number of CSF samples with pleocytosis, increased protein, and decreased glucose concentration. However, four meningococcal and two pneumococcal cases had normal CSF cell count (0-5 cells/mm3), protein (15-45 mg/dl), and glucose (45-80 mg/dl) concentration. Normal CSF cell count cannot always rule out bacterial meningitis. Therefore, diagnosis shouldn’t rely solely on cell count and CSF culture should also be considered.